Effect of zinc (Zn) supplementation on quality and quantity of striped catfish Pangasianodon hypophthalmus sperm - Nunun Ainun Putri Sari Banun Kaliky; Mia Setiawati; Odang Carman; Nur Bambang Priyo Utomo (Jurnal Akuakultur Indonesia)
ABSTRACT